The Effect of Training Variations on Basic Volleyball Passing Skills - Nurapanti, Dena; Hermawan, Irwan; Arifin, Z.; Kosasih, Alam Hadi (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
Objectives. This study aims to determine how the Effect of Exercise Variations on Basic Volleyball Lower Passing Technique Skills. The problem obtained in this study is that there are still many students in volleyball extracurricular activities who are not precise in placing lower passes to their teammates. Materials and Methods. The type of research used is an experiment with a one group pretest and posttest design. The population used was volleyball extracurricular students at SMPN 1 Mekarmukti as many as 10 students. The instrument used is a lower passing ability test with a target that has determining points. The data analysis technique used is the prerequisite test, namely the Kolmogrov-Smirnov test formula to test normality, homogeneity, and the t-test for hypothesis testing at the sig level <0.05. Results. The results of the research on basic volleyball lower passing skills show that there is a significant increase with a variety of basic technique training programs for extracurricular volleyball students, with a t-count value of 5.191> t-table 1.833 (df 9), and a sig value (0.01) <0.05 with an average value of 38.1000. Conclusions. After the research is carried out and based on the analysis with the results, then training using the basic technique training varaisi method can improve the volleyball lower passing skills of extracurricular students of SMPN 1 Mekarmukti. Based on the results of data analysis conducted by researchers, the effect of training variations in basic technical exercises can improve the lower passing skills of volleyball students of SMPN 1 Mekarmukti and there is an increase of 38.1, which is significant.